Sustainable Leadership: The Key to Business Excellence and Innovation - Mumtaz, Asif (2009)
Leaders are an integral part of the communities, organizations and governments. The lack of leadership continuity provides a disruption in an organization’s ability to reach its goals. The cost of recruitment and retention of leaders today are really high but are still nothing as compared to a failed search. Loss of leaders within an organization usually leads to a bye out of the company. It affects the organization both morally and financially. A leader is the one who guides the path for success, without him there is no direction. The literature clearly shows how the average span of CEO’s within organizations is reducing every year. There is an impending shortage of leaders today. This brings about a strong awareness about the topic. Organizations today seek ways to recruit and retain their leaders; they seek a culture bringing about a concept of continuity or sustained wisdom and vision. This is expressed through leadership. This study focuses on determining the qualities of a sustainable leader. The overall approach in studying the common qualities of sustainable leaders was qualitative. A comprehensive review of the literature converged to yield five parallel concepts which formed the basis for deductive analysis. The data analysis led to creating a model for Sustainable leadership which exhibited the five parallel themes and highlighted its attributes. Evolved from these findings a model for the evaluation of Sustainable leadership was framed. The model describes in details the attributes for sustainable leadership. In order to check how the model works, it was applied on an organization to evaluate the level of leadership. A 360 degree review was used as it was a personal and intensive mode of data collection. Interviews, Artifacts and narrative exercises were also x used to provide multiple data points and thus provide cross data validation. Data analysis was accomplished through reduction and subsequently interrater reliability was established. The three sources of data provided a validated and realistic result for the level of leadership present within the organization. This data when referred to the sustainable leadership evaluation model provided a precise explanation of the leadership skills existing within the organization and at the same time indicated areas for improvement. Hence the research fulfills two important objectives; first it provides us with a model for Sustainable leadership, secondly it derives a methodology to measure the level of leadership within an organization. The data from this study could provide new insights into recruitment and retention for leaders and organizations. The five concepts of sustainable leadership outlines in the research form a sustainable leader paradigm which could be useful as an assessment instrument for current leaders and development tool for the emerging and aspiring leaders. The sustainable leadership evaluation model could be used as a guideline for evaluating the level of sustainable leadership within and organization and indicating paths of improvement.